Fusarium soloni mycetoma - V J Katkar; Supriya S Tankhiwale; Arvind Kurhade (Wolters Kluwer Medknow Publications, 2011)
A young apparently healthy, non-diabetic, HIV non-reactive woman presented with a mycetoma-like lesion on right buttock. Discharge was scanty, and mycotic grains were not seen. Biopsy of sinus track was obtained for microscopy and culture. Microscopic examination revealed plenty of fungal hyphae in direct microscopic examination of grounded tissues in saline; KOH, Gram's, and H and E-stained smears. All the three inoculated slants of Sabouraud's media yielded heavy growth of Fusarium solani. Presence of numerous hyphal fragments in direct microscopy and heavy growth of F. solani in all three slants indicative of etiological role of fungus in the present case. It is probably a first report of F. soloni mycetoma from India.